Knife in the back [large type] - Rose, Karen, 1964- (Rose, Karen, 1964- New Orleans novels, 2026)
"Officer Naomi Cranston was framed for stealing cocaine from the evidence locker and coerced-through threats to her young son-into not fighting the charges. After five years in prison, she has tried to put the ordeal behind her, but the crooks who framed her have returned, this time demanding she move drugs along with her flower shop's deliveries. They threaten her son once again, but this time she's not capitulating quietly. She hires Broussard Investigations to protect her and her son, to prove her innocence, and to put the real bad guys away. As a former cop, Burke Broussard is well aware of the corruption in the New Orleans police department. He had always believed Naomi Cranston to be guilty and isn't inclined to take her case. Until he sits down to listen to her side of things. Until he sees her tortured innocence written all over her beautiful face . . . A relationship born amid an investigation is a fragile thing. Will it survive the danger and the threats? Will it survive the truth?"--